Strategic developments in the drug delivery of natural product dihydromyricetin: applications, prospects, and challenges - Ruirui Zhang; Hao Zhang; Houyin Shi; Dan Zhang; Zhuo Zhang; Hao Liu (Taylor & Francis Group, 2022)
Dihydromyricetin (DHM) is an important natural flavonoid that has attracted much attention because of its various functions such as protecting the cardiovascular system and liver, treating cancer and neurodegenerative diseases, and anti-inflammation effect, etc. Despite its great development potential in pharmacy, DHM has some problems in pharmaceutical applications such as low solubility, permeability, and stability. To settle these issues, extensive research has been carried out on its physicochemical properties and dosage forms to produce all kinds of DHM preparations in the past ten years. In addition, the combined use of DHM with other drugs is a promising strategy to expand the application of DHM. However, although invention patents for DHM preparations have been issued in several countries, the current transformation of DHM research results into market products is insufficient. To date, there is still a lack of deep research into the pharmacokinetics, pharmacodynamics, toxicology, and action mechanism of DHM preparations. Besides, preparations for combined therapy of DHM with other drugs are scarcely reported, which necessitates the development of dosage forms for this application. Apart from medicine, the development of DHM in the food industry is also of great potential. Due to its multiple effects and excellent safety, DHM preparations can be developed for functional drinks and foods. Through this review, we hope to draw more attention to the development potential of DHM and the above challenges and provide valuable references for the research and development of other natural products with a similar structure-activity relationship to this drug.